1990
DOI: 10.1164/ajrccm/142.3.523
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk, and Prognosis Factors of Nosocomial Pneumonia in Mechanically Ventilated Patients

Abstract: Seventy-eight (24%) episodes of nosocomial pneumonia (NP) were detected in 322 consecutive mechanically ventilated patients admitted to a 1,000-bed teaching hospital from April 1987 through May 1988 to assess the incidence, risk, and prognosis factors of NP acquired during mechanical ventilation (MV). The risk and prognosis factors for developing NP during MV were studied using both univariate and multivariate statistical techniques. Multivariate analysis selected the following variables significantly associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
324
5
23

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 844 publications
(379 citation statements)
references
References 8 publications
22
324
5
23
Order By: Relevance
“…These circumstances are outlined in Table 5 (198,215). However, either such scenarios are uncommon or the procedures required are undesirable or contraindicated in critically ill patients on mechanical ventilators.…”
Section: Treatmentmentioning
confidence: 99%
“…These circumstances are outlined in Table 5 (198,215). However, either such scenarios are uncommon or the procedures required are undesirable or contraindicated in critically ill patients on mechanical ventilators.…”
Section: Treatmentmentioning
confidence: 99%
“…Further, the use of the EtView device requires reintubation. A previous study identified reintubation as an independent risk factor for ventilator-associated pneumonia [19]. Whilst microaspiration of contaminated secretions during reintubation might explain the association between reintubation and VAP, no difference was made in that study between reintubation for weaning failure, accidental extubation, or planned reintubation.…”
mentioning
confidence: 80%
“…Association of germs in lung biopsy culture occurred only in four patients (see Table 1). Most published studies have pointed out the polymicrobial status of nosocomial pneumonia (26,27). Bartlett et al (26) found polymicrobial pneumonia in 54% of 159 cases.…”
Section: Discussionmentioning
confidence: 99%